THE UTILISATION OF ZAKAT FOR AMBULANCE OPERATIONS: A CRITICAL STUDY OF THE ACEH BRANCH OF RUMAH ZAKAT - Abdul Jalil Salam; Aulia Rivaldi (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2018)
Zakat distribution is one of the factors used as a benchmark for Muslims to choose an institution that is trusted in the management of zakat. The concern of Muslims that the existing funds reach or not to the rightful ones is often the cause of the lack of empowerment of existing amil institutions. There are three research questions in this study, namely first, how is the free ambulance financing system applied by the Aceh branch of Rumah Zakat. Second, how is the target of free ambulance services applied by Rumah Zakat Aceh branch, and third, how is the Islamic legal review of the utilization of zakat funds senif fī sabīlillāh for the operation of the free ambulance programme according to Yūsuf Qardāwī's perspective on Rumah Zakat Aceh branch. This research uses descriptive analysis research method, namely by discussing the problems that arise now to be analysed for solutions based on books and sources related to the title discussed and then looking for solutions, data collection is done using interviews and observations. The results showed that first, the financing for the free ambulance was borne by Rumah Zakat Aceh Branch through the utilisation of zakat funds for the benefit of the people whose portion was taken from Senif Fī Sabīlillāh. This is done to reduce the burden on people who need free ambulance assistance provided by Rumah Zakat. Second; The target of free ambulance services provided by Rumah Zakat Aceh branch is for all people in need, and Rumah Zakat serves people who need free ambulance services for 24 hours a week. Third, Islamic law allows the use of zakat funds for the free ambulance programme, because the free ambulance programme is also included in the programme to improve the benefit of the people. In this case, Yūsuf Qard̟āwī allows the use of zakat funds for public benefits.